An Annotated Report of Mites Infesting Medicinal Plants of West Bengal, India - Roy, Indranil; Aditya, Gautam; Gupta, Saul Kumar; Saha, Goutam Kumar (Journal of the Bombay Natural History Society (JBNHS), 2011)
No Abstract.